Real-World Outcomes of Direct-Acting Antiviral Treatment and Retreatment in United Kingdom–Based Patients Infected With Hepatitis C Virus Genotypes/Subtypes Endemic in Africa . (1st March 2021) - Aranday-Cortes, Elihu; McClure, C Patrick; Davis, Christopher; Irving, William L; Adeboyejo, Kazeem; Tong, Lily; da Silva Filipe, Ana; Sreenu, Vattipally; Agarwal, Kosh; Mutimer, David; Stone, Benjamin; Cramp, Matthew E; et al.
Abstract: Background: Chronic hepatitis C virus (HCV) infection affects 71 million individuals, mostly residing in low- and middle-income countries (LMICs). Direct-acting antivirals (DAAs) give high rates of sustained virological response (SVR) in high-income countries where a restricted range of HCV genotypes/subtypes circulate. Methods: We studied United Kingdom–resident patients born in Africa to examine DAA effectiveness in LMICs where there is far greater breadth of HCV genotypes/subtypes. Viral genome sequences were determined from 233 patients. Results: Full-length viral genomic sequences for 26 known subtypes and 5 previously unidentified isolates covering 5 HCV genotypes were determined. From 149 patients who received DAA treatment/retreatment, the overall SVR was 93%. Treatment failure was associated primarily with 2 subtypes, gt1l and gt4r, using sofosbuvir/ledipasvir. These subtypes contain natural resistance-associated variants that likely contribute to poor efficacy with this drug combination. Treatment failure was also significantly associated with hepatocellular carcinoma. Conclusions: DAA combinations give high SVR rates despite the high HCV diversity across the African continent except for subtypes gt1l and gt4r, which respond poorly to sofosbuvir/ledipasvir. These subtypes are widely distributed across Western, Central, and Eastern Africa. Thus, in circumstances where accurate genotyping is absent, ledipasvir and its generic compounds should not be considered as a recommended treatment option. Abstract : We examined hepatitis C virus (HCV)–infected patients born in Africa but resident in the United Kingdom for treatment outcomes for direct-acting antiviral therapy. The unusual HCV subtypes identified in many patients successfully responded to treatment except for 2 subtypes.